USING THE THEORY OF PLANNED BEHAVIOR TO UNDERSTAND PADDY RICE FARMERS' INTENTION TO PARTICIPATE IN WAREHOUSE RECEIPT SYSTEM - Permana, Anggit Jati; Sampurna, Agung Firman; Wijaya, Chandra; Ulum, Bachrul (Universitas Negeri Yogyakarta, 2023)
The Warehouse Receipt System (WRS) is one of the tools available for farmers to combat commodity price instability that often happens during harvest season. The WRS Program, complemented by the WRS Subsidy Scheme, has already been implemented in Indonesia for almost fourteen years with minimum participation from the farmers. This research uses a model based on the Theory of Planned Behavior to understand factors affecting the intention level of paddy rice farmers in Demak to participate in the WRS Program. This research employs a quantitative approach, collecting data using surveys to sample farmers from Demak and Dempet Subdistricts and analyzing it using descriptive analysis and SEM-PLS. This research found a small yet positive intention of paddy rice farmers in Demak to participate in the WRS Program. All direct and indirect determinants of intention based on the TPB positively affect farmers' intention to participate in the WRS Program. This research also suggests improving farmers' intention to participate in the WRS Program. The government is advised to build more facilities in the WRS Program warehouse to make it easier for farmers to store their commodities in the WRS warehouses, increasing their perceived behavioral control. The government needs to focus on and increase the frequency of information-sharing sessions regarding the WRS Program to improve farmers' attitudes, subjective norms, and perceived behavioral control. The government can also explore other policy instruments besides the WRS Subsidy Scheme, such as the Nudge to improve farmers' participation In the WRS Program.